MÍDIA E MARKETING POLÍTICO: A CAMPANHA ELEITORAL DE FERNANDO HENRIQUE CARDOSO PARA PRESIDENTE, NAS PÁGINAS DA REVISTA VEJA EM 1994 - Cunha, Jorge Vidigal da (2010)
The goal of this essay is to verify, according to the concepts of political marketing, how did the construction of the public image of the ex-president Fernando Henrique Cardoso happened in the Veja magazine during the elections of 1994. To fulfill this project, it was investigated 19 editions, relative to the period of June to October of the referred year. It was studied the ideological propaganda and its categories, such as codification, ideological control, counterpropaganda and diffusion, all present in the analyzed material. This work was developed in the light of the methodological procedures referred to the Study of Case as a type or research strategy. Among the techniques for collecting data, it was held the Content Analysis of quantitative and qualitative nature of the data researched and the interview with the ex-president. Furthermore, this study obtained the following results: Fernando Henrique Cardoso had the majority of the volume in centimeter/column in relation to his opponent, the candidate Luiz Inácio Lula da Silva. Regarding the codes used in the analyzed material, the bulk volume in centimeter/column occurred in the linguistic code, meaning that Veja magazine gave more attention to the words, sentences and even the paragraphs which composed the articulated structures, following the historic and cultural patterns of the Portuguese language. Concerning the informative genre, the biggest share in centimeter/column was in news report, designating that Veja magazine emphasized the facts that echoed and produced effects on society, and were memorable by the magazine s point of view. It is possible to reckon that the published material strengthened significantly his image before the Veja readers, favoring him in relation to his opponent, however didn t really elect him.(AU)